1982
DOI: 10.1029/ja087ia08p06137
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical magnetograms based on quantitative simulation of a magnetospheric substorm

Abstract: Using substorm currents derived from the Rice computer simulation of the substorm event of September 19, 1976, we have computed theoretical magnetograms as a function of universal time for various stations. A theoretical Dst has also been computed. Our computed magnetograms were obtained by integrating the Biot‐Savart law over a maze of approximately 2700 wires and bands that carry the ring currents, the Birkeland currents, and the horizontal ionospheric currents. Ground currents and dynamo currents were negle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“… Chen et al [1982] predicted that the day‐night net Birkeland currents flow into the ionosphere around 1100 LT and flow out around 2200 LT. The local time distribution of the net current system can be derived from Figures 4 and 5 because the orbits of the Oersted satellite cover various local time sectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Chen et al [1982] predicted that the day‐night net Birkeland currents flow into the ionosphere around 1100 LT and flow out around 2200 LT. The local time distribution of the net current system can be derived from Figures 4 and 5 because the orbits of the Oersted satellite cover various local time sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the total intensity of the region 1 and the region 2 Birkeland currents are the same, the net Birkeland currents flow into the Earth's ionosphere around the noon and flow out around the midnight by the Hall conductivity effect. Chen et al [1982] predicted from their quantitative simulation of current system in the inner magnetosphere that the net Birkeland currents flow into the ionosphere around 1100 LT and flow out around 2200 LT, which is schematically illustrated in Figure 1a. The day‐night net Birkeland currents make the latitudinal profile of the magnetic field variation, Δ B ϕ , as illustrated in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%
“…This view seems, at first glance, to be in conflict with the main-phase ground-magnetometer observations. However, Crooker and Siscoe (1981), Harel et al (1981b) and Chen et al (1982) argued that it is not. They showed that the observed asymmetry can be explained quantitatively by the idea that the sum of region-1 and region-2 Birkeland currents is downward on the dayside and a net upward on the night side.…”
Section: Developments In Understanding Magnetic Storms and The Ring-cmentioning
confidence: 93%
“…the net field-aligned currents resulting from unbalanced Region 1 and Region 2 currents. These have been theoretically hypothesised by Crooker and Siscoe (1981) and by Chen et al (1982) to explain the dawn-dusk asymmetry of the disturbance observed in the north-south geomagnetic component and the features of the disturbance observed in the east-west component at low and mid-latitudes. Evidences of net field-aligned currents have been discovered later in satellite observations (e.g.…”
Section: Resultsmentioning
confidence: 99%